Residual cannabis levels in blood, urine and oral fluid following heavy cannabis use - Odell, Morris S.; Frei, Matthew Y.; Gerostamoulos, Dimitri; Chu, Mark; Lubman, Dan I. (Forensic science international, 2015)
•Twenty-one dependent cannabis users were recruited for this study.•Daily blood, urine and oral fluid samples were collected for seven consecutive days.•THC was detected in oral fluid up to 3 days after cessation of use.•THC was detectable in blood for at least 7 days after admission to the unit.•Interpretation of residual THC levels in cannabis users may need to be reconsidered. An understanding of tetrahydrocannabinol (THC) kinetics and residual levels after cannabis use is essential in interpreting toxicology tests in body fluids from live subjects, particularly when used in forensic settings for drug abuse, traffic and interpersonal violence cases. However the current literature is largely based on laboratory studies using controlled cannabis dosages in experienced users, with limited research investigating the kinetics of residual THC concentrations in regular high dose cannabis users. Twenty-one dependent cannabis users were recruited at admission to two residential detoxification units in Melbourne, Australia. After being provided with information about, and consenting to, the study, subjects volunteered to provide once-daily blood, urine and oral fluid (saliva) samples for seven consecutive days following admission, involving cessation and abstinence from all cannabis use. Blood and oral fluid specimens were analysed for THC and urine specimens for the metabolite THC-COOH. In some subjects THC was detectable in blood for at least 7 days and oral fluid specimens were positive for THC up to 78h after admission to the unit. Urinary THC-COOH concentrations exceeded 1000ng/mL for some subjects 129h after last use. The presented blood THC levels are higher and persist longer in some individuals than previously described, our understanding and interpretation of THC levels in long term heavy cannabis users may need to be reconsidered.